PEMANFAATAN SMARTPHONE DAN MAINAN ELEKTRONIK SEBAGAI MEDIA PEMEROLEHAN BAHASA PADA ANAK USIA DINI - Zulwahdini Zulwahdini; Nensilianti Nensilianti; Andi Sahtiani Jahrir (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the development of early childhood vocabulary in the utilization of smatrphones and electronic toys as a media for language acquisition. This type of research is qualitative. The data of this research is in the form words derived from the utilization of thes media. The data source of this research is children aged 4-6 years who are sitting ini Kartika XX-12 Kindergarten, Parepare City. The approach used is Noam Chomsky’s Psycholinguistics. The results of this study show that there arenfour types of word categories obtained by children in the use smartphones and electronic games as media for their language acquisition consisting of nouns, verbs, adjectives, and adverbs.